Comparative studies of free and immobilized phytase, produced by Penicillium purpurogenu GE1, using grafted alginate/carrageenan beads - Awad, G.; Esawy, M.; El-Gammal, E.; Ahmed, H.; Elnashar, Magdy; Atwa, N. (2015)
Aim: The aim of the study was to immobilize the phytase enzyme produced by Penicillium purpurogenu GE1 on grafted alginate/carrageenan beads and study the properties of the immobilized enzyme in comparison with free ones. Materials and methods: The immobilization conditions were first optimized and then the optimum conditions of temperature and pH for the maximum activity of the immobilized and free enzyme were studied and compared. The stabilities of both immobilized and free phytase at moderate and low temperatures of 50 and 4°C, as well as their stability at the acidic pH of 4, were also studied. Finally, the activity of the immobilized enzyme was monitored over 20 successive repeated batches. Results: The maximum loading capacity was obtained after 20 h at the enzyme/acetate buffer dilution ratio of 1 : 2. The optimum temperature and pH of the immobilized enzyme, as compared with free state, were found to have shifted from 37 to 45°C and from pH 5.5 to 4, respectively. Moreover, the results also proved that when phytase in both immobilized and free states was subjected to an acidic pH of 4 for 45 min, or to a moderately high temperature of 50°C for 60 min, the activity of the former remained stable, whereas that of the latter showed substantial losses. In contrast, at the refrigerator shelf temperature of 4°C, dry and wet immobilized forms retained 100% activity for 12 weeks, whereas that of the free enzyme was completely lost within a shorter period of 4 weeks. Furthermore, the activity of the phytase enzyme immobilized on gel beads was maintained at the 100% level for more than 12 repeated batch utilizations of the beads. Conclusion: The results revealed that the physiological parameters of the immobilized enzyme were greatly improved compared with the free state. Further, the activity of the phytase enzyme immobilized on gel beads was maintained at the 100% level for more than 12 repeated batch cultivations of the beads.